Pengaruh Kompensasi dan Motivasi Kerja Terhadap Kinerja Karyawan pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Karawang - Rizqa Aulia Islami; H. Asep Jamaludin; Nandang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of compensation and work motivation on employee performance at the Karawang Regency Personnel and Human Resources Development Agency (BKPSDM). The method used was quantitative descriptive sampling, which used saturated sampling, while obtaining data was carried out by distributing questionnaires to 53 employee respondents BKPSDM who then analyzed the influence partially and simultaneously using Path Analysis of the coefficient of determination as well as testing the t test and f test. The research results show that: the influence of compensation and work motivation on employee performance is positive and significant, so the compensation path coefficient is 0.888, which means that compensation is greater than the motivation variable, namely 0.172, which means that motivation has a greater influence on employee performance. Based on the research results, it can be concluded that compensation partially influences the performance of Karawang Regency employees BKPSDM. Motivation influences employee performance at BKPSDM Karawang Regency and simultaneously compensation and work motivation influence employee performance at BKPSDM Karawang Regency.